2017
DOI: 10.5138/09750185.2115
|View full text |Cite
|
Sign up to set email alerts
|

Analgesic and acute inflammation properties of the aqueous extract of dried leaves of <em>Paullinia Pinnata</em> (Sapindaceae) Linn

Abstract: <p align="left">Inflammation is frequently associated with pain. Plants continue to be major resources for therapeutic compounds against various diseases including inflammation and pain. <em>P</em><em>aullinia Pinnata </em>is used to treat several diseases, including rheumatism and abdominal pain. This study was undertaken to assess the analgesic and anti-inflammatory effects of <em>P</em><em>aullinia Pinnata. </em>The analgesic activity was evaluated by us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 19 publications
(23 reference statements)
0
1
0
Order By: Relevance
“…Lunga et al, [60] reported the antithypoid and free radical scavenging properties of methanol extracts from the aerial part of P. pinnata. Patience et al, [61] observed the antiinflammatory activity of the aqueous extract of the leaves part of P.pinnata.…”
Section: Pharmacological Activities Of Nigerian Medicinal Plantsmentioning
confidence: 99%
“…Lunga et al, [60] reported the antithypoid and free radical scavenging properties of methanol extracts from the aerial part of P. pinnata. Patience et al, [61] observed the antiinflammatory activity of the aqueous extract of the leaves part of P.pinnata.…”
Section: Pharmacological Activities Of Nigerian Medicinal Plantsmentioning
confidence: 99%